Effects of synbiotic supplement in Thai smokers: A preliminary study - Parama Pratummas (2020)
© 2019 IEEE. this study proposes the effect of synbiotic supplement on gut-brain axis in Thai smokers in the realm of gut-related biochemical parameters and cognition. We conducted a single group, pre- and post-test study; 20 patients lived in Mahasarakham, Fagerstrom Test for Nicotine Dependence at 4 or above, and no history of cerebrovascular diseases, brain and abdominal surgery, and not taking hormones or drugs influenced brainwaves or using antibiotics within two weeks before. Subjects were assigned to intake synbiotic supplement containing 3 types of prebiotics and 7 species of probiotics once a day before bedtime for 8 weeks. Outcomes were measured in gut-related biochemical parameters change and alternation in cognition. The current results have shown significantly decrease in the scores of Fagerstrom test for nicotine dependence and also the scores of craving for smoke after intervention. Further studies are mandatory to conduct in finding a tendency to improve in gut-related biochemical parameter and cognition after intake of synbiotic supplement.